PENERAPAN MANAJEMEN KEPALA SEKOLAH TERHADAP PENERAPAN METODE KOOPERATIF MODEL GROUP INVESTIGATION SEBAGAI ALTERNATIF MENINGKATKAN KINERJA GURU MENGAJAR DI SDN INPRES MANDOK: SDN IMPRES MANDOK, KECAMATAN BULAGI UTARA, KABUPATEN BANGGAI KEPULAUAN - HIRENTO SOILO (Dewan Pendidikan Bondowoso, 2022)
By taking into account the formulation of the problem above, the objectives of this study are 1). Want to know the improvement of teacher performance after the implementation of the Group Investigation model of cooperative learning at SDN Inpres Mandok, North Bulagi District, Banggai Islands Regency 2). Want to know the effect of student learning motivation after applying the Group Investigation model of cooperative learning at SDN Inpres Mandok, North Bulagi District, Banggai Islands Regency The type of research used by the author in this research is school action research. According to Arikunto (Suyadi, 2012), PTS is a combination of understanding from the words